PERSEPSI MANAJER ATAS INFORMASI AKUNTANSI KEUANGAN DAN PENGARUHNYA PADA KEBERHASILAN MENGELOLA PERUSAHAAN KECIL DAN MENENGAH DI SURABAYA - Ira Purwanti; Gunasti Hudiwinarsih (Universitas Hayam Wuruk Perbanas, 2012)
The smooth cash flow in financial accounting information of small or medium enterprises is beneficial for understanding the business development company, the capital structure, and profits a company that has been obtained in a given period. The more experience a manager of financial accounting information has, the better the ability of a manager to manage his company. For that reason, this research attempts to identify the factors influencing the perception of a manager of financial information on the success of managing small and medium enterprises (SMEs) in Surabaya. The research was conducted by questionnaire on distributed to the managers (owners) of small and medium enterprises in the industrial small and medium of bags and shoes in Surabaya with the total number of 110 people. This is quantitative analysis by implementing Structural Equation Modeling (SEM). The results showed that the proven factors that include the manager's perception of attitude, personality, motivation, and experience has an influence on perceptions of a manager of financial accounting information and also determine whether the perception of a manager of financial accounting information has influence on the success of managing small company and medium enterprises in Surabaya.